Learning Strategies for Early Children with Special Needs - Fenty Andriani; Yuli Salis Hijriyani (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2020)
This article is intended to reveal the importance of learning strategies for children with special needs. The results of literature review show that there are some learning strategies that can be used in the teaching and learning process for children with special needs. Those learning strategies cover: First, perceptual-motor training, such as training the ability to distinguish shapes, symbols, letters, etc. and training on the ability to remember. Second, auditive, such as training children to distinguish consonant and vowel sounds. Third, modeling which is a learning activity by following the styles of others as a model and being able to imitate the behavior of teachers or parents.